Male chimpanzee sexual coercion and mating success at Ngogo. Issue 2 (14th January 2022) - Watts, David P.
Abstract: Chimpanzees ( Pan troglodytes ) have a complex mating system in which both sexes use multiple tactics. Most copulations occur in group contexts, and high‐ranking males can gain high mating and reproductive success, but females typically mate with multiple males and the potential for sperm competition is high. Also, male‐female dyads sometimes form temporary exclusive mating associations (consortships). Male aggression to receptive females is common. Several studies have supported the hypothesis that this is sexual coercion, but debate exists regarding the importance of coercion relative to that of female choice. The number of adult males in a community can influence the balance between these processes. In the large Ngogo community, male dominance ranks and rates of aggression to fully‐swollen females were positively related to mating success as estimated by copulation rates and by proportions of copulations achieved. Aggression rates were higher than at other sites, overall and per male, especially during periovulatory periods, and increased with the number of males associating with a female. Aggression impaired female foraging efficiency. Males initiated most copulations and females rarely refused mating attempts. Male‐to‐female grooming was positively associated with male mating success and with the proportion of copulations that females initiated, but the amount of grooming was typically small and whether grooming‐for‐mating trading occurs is uncertain. These results are consistent with the hypothesis that sexual coercion is an important component of male chimpanzee mating strategies in many sociodemographic circumstances, but also show that male tactics vary both in response to and independently of those circumstances. RESEARCH HIGHLIGHTS: 1. Both male and female chimpanzees use multiple mating tactics. Most mating occurs when females are with multiple males and copulate with most or all of them. The potential for contest and scramble competition among males is high in this context. 2. Males also are often aggressive to receptive females, which can constrain mate choice and impose other costs. Data from the extremely large Ngogo community in Kibale National Park highlight the importance of sexual coercion as a male mating tactic. 3. Male mating success at Ngogo was positively associated with rates of male aggression to females. Receptive females received aggression at unusually high rates, especially when they were periovulatory and were with many males. Male aggression impaired female foraging efficiency. Mating success also increased with male dominance rank. 4. Mating success also was positively related to the amount of male‐to‐female grooming, possibly adding to evidence that social relationships are important in chimpanzee mating strategies, but grooming was infrequent and any effect was small. 5. The results provide further evidence that demographic variation influences variation in chimpanzee mating strategies. Abstract :